Immigration Policy and Gender of “Talent”: Iranian Musicians’ Mobility towards France via the Passeport talent - Jafarinejad, Kayvan (Intersections, 2022)
This article explores how gender affects the (im)mobility of Iranian women musicians who seek to pursue their careers in France with the passeport talent (talent passport) visa. It first examines the socio-professional conditions of women musicians in Iran and then analyzes France’s migration policies and its gender-related (dis)advantages for international artists. Not only do women’s bodies face systemic censorship in Iran, but they are also neglected in French migration policies due to a formal approach that fails to take into account substantive gender differences. Thus, the study sheds light on the complex interplay between the concept of gender and power relations in both the Iranian and French contexts.